Avaliação da eficiência do ensino contextualizado de educação ambiental no Colégio de Aplicação da Universidade Federal de Sergipe - UFS - Santos, Carlos Frederico Resende da Costa (2016)
Environmental Education (EE) is proposed Federal Constitution (BRASIL, 1988) at all educational levels, and should be present in formal learning environments and non-formal. The Parâmetros Curriculares Nacionais (PCN's), containing the guidelines to be adopted by primary schools from 1997 to treat environmental education as a cross-cutting issue to be worked in all disciplines. This document suggests ways of introduction of environmental education in school curricula, and also highlights the environmental concerns and contemplate local realities. In this sense, the hypothesis that guides this study is that the Colégio de Aplicação (CODAP) of Universidade Federal de Sergipe adopts EE in all fields of knowledge in an interdisciplinary way. Thus, the general objective of this research is to evaluate the efficiency of contextualized environmental education teaching, according to the recommendations of the Parâmetros Curriculares Nacionais theme Environment, the Colégio de Aplicação of UFS, with the following objectives: to identify the difficulties of contextual teaching and learning model on the theme Environment and consequently the EE; develop a profile of the students on the level of knowledge related to environmental issues. This research was conducted in the Colégio de Aplicação (CODAP) of the Universidade Federal de Sergipe, located in São Cristóvão. The methodology of this study followed a prospective descriptive, qualitative and quantitative, which favored the collection of information about the object of study. site visits were conducted for analysis of its Political Pedagogical Project (PPP) and application of a questionnaire to teachers and students in order to collect data about the EE. From the results was carried out a comparison between the performance of students and teachers' responses and the goals of the PCN's about the cross-environment theme as a strategy for the development of school activities. It was observed the absence of an EE project in the curriculum of elementary college education, because it has a direct relationship with the school's peculiarities and the immediate living conditions of students. However, there are specific events in the disciplines Sciences and Geography, with predominant orientation of informative and unrelated nature of the goals of the PCN‟s. Finally, it was found that EE is not practiced in an interdisciplinary way and, much less, the cross-environment theme is working in all disciplines, as proposed by the PCN's, as the faculty demonstrated not incorporate the changes suggested by the document. Teachers, mostly claim they do not feel safe in dealing with these practices by the lack of training offered by the college. In addition, the Pedagogical Political Project (PPP) of CODAP does not include EE practices for the subjects.